Uncertainty in risk assessment : the representation and treatment of uncertainties by probabilistic and non-probabilistic methods - Aven, Terje (Chichester, West Sussex, UK : Wiley, 2014)
"There are a growing number of researchers and analysts who find the probability-based approaches for assessing risk and uncertainties to be too narrow and limiting. Uncertainty in Risk Assessment provides a broad conceptual framework and describes various alternative approaches of uncertainty representation and characterization therein such as probability-bound analysis, imprecise probability and evidence theory. The authors, whose own research has been at the forefront of developments in the field, include a number of real-life applications which demonstrate the practical use of the various methods in the different realistic circumstances. They provide invaluable practical guidance and clear recommendations on how and when to use the various approaches"--
"Uncertainty in Risk Assessment addresses an important and current problem for which there are competing solutions"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Risk assessment -- Statistical methods; Probabilities; MATHEMATICS -- Probability & Statistics -- General; Probabilities; Risk assessment -- Statistical methods; Electronic books